Psychological distress, loneliness, and satisfaction with life during the COVID-19 pandemic: a longitudinal study comparing migrants and non-migrants in Norway - Benavente, Pierina; Fadnes, Lars Thore; Sandal, Gro M.; Mæland, Silje; Lehmann, Stine; Diaz, Esperanza (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic disproportionately impacted migrants’ health and well-being, with some effects becoming evident months into the crisis. Psychological distress, loneliness, and satisfaction with life, which are indicators closely tied to mental health and well-being, were critically affected during the pandemic. However, comparative longitudinal studies of these parameters across migrant and non-migrant population remain scarce. This study compares the evolution of psychological distress, loneliness, and satisfaction with life during the pandemic between migrants and non-migrants in Norway.MethodsWe performed a secondary analysis of data from three timepoints (March/April-2020, January-2021, March-2022) of the Bergen in Change study. The sample included 25,412 participants, with 512 (2%) migrants from Asia, Africa, or Latin America and 1,253 (5%) migrants from other regions. Psychological distress, loneliness, and satisfaction with life were measured using the Hopkins Symptom Checklist-10, the UCLA loneliness scale, and UK Office of National Statistics experimental evaluative subjective well-being question, respectively. Analyses included descriptive statistics, box plots, and linear mixed regressions presented with coefficients and 95% confidence intervals.ResultsAt baseline, migrants reported higher levels of psychological distress and loneliness compared to non-migrants. Specifically, migrants from Asia, Africa and Latin America reported 6.0% higher psychological distress and 7.7% higher loneliness than non-migrants, while migrants from other regions reported 4.3 and 5.4% higher levels, respectively. The evolution of both outcomes differed over time. The absolute gap of psychological distress between migrants to non-migrants narrowed by 1.4% per year for migrants from Asia, Africa and Latin America [−1.4(−2.4; −0.3)] and by 0.8% for migrants from other regions [−0.8(−1.4; −0.2)]. In contrast, differences in loneliness between migrants from other regions and non-migrants increased by 1.5% per year [1.5(0.2; 2.9)]. Satisfaction with life did not differ significantly between groups and showed similar trends over time.ConclusionHigher burden of psychological distress and loneliness were consistently reported by migrants compared to non-migrants throughout the pandemic, while levels of satisfaction with life remained similar across groups. Differential changes over time in psychological distress and loneliness were also observed. These patterns may reflect the influence of underlying factors such as resilience, social isolation, and discrimination.